Densification and structural transformation during spark plasma sintering of WC-Co-YSZ-cBN systems. (April 2018) - Langa, Thabiso; Olubambi, Peter; Shabalala, Thembinkosi; Shongwe, Mxolisi Brendon
Abstract: The demand for enhanced materials with high hardness, strength and wear resistance have become critically important in the cutting tool industry. WC-Co cermets are hard metals that possess a combination of excellent mechanical properties and high fracture toughness. However, WC-Co has specific limits in application as a structural component were high temperature strength, oxidation and corrosion resistance are required. Efforts have been made to replace cobalt with nickel or iron binder. WC-Ni has shown to possess better corrosion and oxidative resistance than WC-Co and WC-Fe, however it has lower mechanical properties compared to WC-Co. WC-Fe has inferior oxidative and corrosion to WC-Co and WC-Ni. Recent studies have recently been reported on the use of zirconia, having good binding strength and adhesion with the matrix, as a novel binding phase for WC. This study focusses on the partial replacement of cobalt with milled ZrO2 stabilized with 7.5 wt% Y2 O3 (YSZ) reinforced with cubic boron nitride (cBN). The synthesis focuses on full densification of 4 different compositions (WC-Co (control sample), WC-Co-YSZ, WC-Co-cBN and WC-Co-YSZ-cBN) using spark plasma sintering all at 1300 °C and 50 MPa with the goal of developing a WC-YSZ-cBN composite with no or little sintering aid. The effect of isothermal holding time on the densification, mechanical properties and microstructural & phase evolution were studied and will be presented. The results show that full densification, retention of tetragonal-YSZ phase, no cBN to hBN phase transformation and improved hardness & fracture toughness was obtained on the newly developed composite. Highlights: Cobalt binder content is a significant driver for densification. No cBN to hBN phase transformation observed. High relative densities and the addition of YSZ and cBN are responsible for the high hardness of ~ 20 GPa obtained. Excellent fracture toughness of ~ 9 MPa.m 1/2 obtained is due to the high retention of the tetragonal phase.